Empowerment of Poklahsar Anggun Through Diversification of Seasoned Pressure-Cooked Fish Based on Blue Economy in Lekok Hamlet, North Lombok Regency - Agustina, Shelly Sylvia; Kasia, Mutiara Mita; Jamil, Farah Ainun; Nasution, Ade Rezkika; Shahab, Mohammad Alwi; Putu Bayu Paramayuda, I Gusti (Jurnal Pengabdian West Science, 2026)
This community service program focused on empowering coastal communities through the diversification of seasoned pressure-cooked scad fish products based on the blue economy concept in Dusun Lekok, North Lombok Regency. The program aimed to improve community knowledge, technical skills, and economic independence in fishery product processing. The activities were conducted using a participatory and sustainable approach involving counseling, training, hands-on practice, mentoring, monitoring, and evaluation. The implementation covered raw material selection, hygienic fish handling, seasoning formulation, pressure-cooking techniques, vacuum packaging, and product labeling. The results indicated significant improvements in participants’ understanding and practical skills in fish processing, sanitation, packaging, and product quality enhancement. In addition, the program strengthened group participation, increased entrepreneurial motivation among coastal women, and promoted sustainable utilization of marine resources through value-added fishery products with higher economic potential.
Keywords: Blue economy; fish diversification; coastal women empowerment; community empowerment